Association of premature menopause with incident pulmonary hypertension. (25th November 2020) - Honigberg, M; Lahm, T; Wood, M; Ho, J; Kohli, P; Natarajan, P
Abstract: Background: Several forms of pulmonary hypertension (PH) disproportionately affect women. Prior animal and human studies suggest that oestradiol exerts mixed effects on the pulmonary vasculature. Whether premature menopause represents a risk factor for PH is currently unknown. Purpose: To test the independent association of premature menopause with incident PH. Methods: We included women in the UK Biobank who were 40–69 years old and postmenopausal at enrolment and underwent pulmonary function testing at the baseline study visit. Women with missing menopause data, prevalent PH, extreme pulmonary function test outliers (Z>5 or Z<−5), and those with congenital heart disease were excluded. Premature menopause was defined as occurring before age 40 years. Reproductive history, including age at menopause and use of menopausal hormone therapy (MHT), was ascertained by participant self-report at enrolment. PH risk factors and relevant co-morbidities were captured by participant self-report and by ICD code. Incident PH was ascertained by the appearance of a qualifying ICD code (ICD-9 4160; ICD-10 I27.0, I27.2). Follow-up began at study enrolment, with time to censoring determined by date of PH diagnosis or last encounter in the medical record. Multivariable Cox proportional hazard models tested the association between premature menopause and incident PH, with adjustment for age, race, ever-smoking, body-mass index, systolic blood pressure, antihypertensive medication use, non-high-density lipoprotein cholesterol, cholesterol-lowering medication use, C-reactive protein, prevalent type 2 diabetes, obstructive sleep apnoea, heart failure, venous thromboembolism, mitral regurgitation, aortic stenosis, forced vital capacity (FVC), the forced expiratory volume in 1 second (FEV1)/FVC ratio, and ever-use of MHT. Results: Among 138, 518 postmenopausal women (mean [SD] age at enrolment 60.0 [5.4] years), 5, 440 women (3.9%) had a history of premature menopause. Incident PH was diagnosed in 253 women over a median 8.1 (interquartile range 7.4–8.8) years of follow-up. Mean age at menopause was 48.3 (6.4) years among women with incident PH vs. 49.7 (5.1) years among those without PH (P<0.001). Crude cumulative incidence of PH was 0.40% among women premature menopause vs. 0.17% among those without (Figure 1). After multivariable adjustment, premature menopause remained independently associated with PH (hazard ratio [HR] 1.91, 95% CI 1.15–3.16, P=0.01). Ever-use of MHT was not significantly associated with incident PH (HR 0.93, 95% CI 0.68–1.26, P=0.62). In sensitivity analysis excluding 4, 461 women with prevalent heart failure, venous thromboembolism, mitral regurgitation, or aortic stenosis, the HR for PH associated with premature menopause was 2.19 (95% CI 1.28–3.74, P=0.004). Conclusions: Premature menopause is an independent risk factor for PH in women. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): U.S. National Heart, Lung, and Blood Institute